2021 PIM partnership evaluation - Andersson, Krister; Templeton, Deborah (International Food Policy Research Institute, 2021)
The evaluative study focuses primarily on PIM’s external partners; this includes partnerships where PIM is engaged by another organization as a service provider and trusted advisor. The objective is to undertake an in-depth analysis of PIM partnerships and to elicit lessons on the key factors contributing to their success in achieving outcomes. The aim is to generate: (1) an inventory of partnerships; (2) an understanding of the motivations for partnership formation, and of the partnership dynamics in promoting innovations and change; and (3) an assessment of strengths, weaknesses, and opportunities to foster stronger future partnerships. This evaluative study serves the dual purposes of accountability to CGIAR partners and funders and of learning. The primary intended users are CGIAR researchers and partners. The findings and lessons learned will also provide input into the implementation of new initiatives under One CGIAR.